Effect of Post Heated TiN Coating on Pitting Corrosion of Austenitic Stainless Steel (Journal of Coating Science and Technology, 2016)
This study used cathodic arc deposition technique to coat TiN film on 316L austenitic stainless steel, and then the coated specimens were heat-treated at the different temperatures. Observation of coating morphology and corrosion tests were conducted for exploring the effect of post-heating temperature on composition, microstructure, and corrosion behavior of the coatings. The results showed when the heating temperature was up to the range of 500-600 oC, a Ti-N-O mixed film consisting of the two TiO2 and TiN phases was formed on the outer layer. Particular, the film heated at 500 oC had a dense structure as well as homogeneous chemical composition. Such the result could effectively inhibit pitting corrosion of 316L stainless steel in 3.5 wt% NaCl and 10 vol% HCl solutions.